PENGEMBANGAN MEDIA POP-UP MENGGUNAKAN BARCODE MATERI EKOSISTEM DAN JARING-JARING MAKANAN UNTUK SISWA KELAS V SEKOLAH DASAR - Retno Laely; Ita Kurnia; Farida Nurlaila Zunaidah (JS (JURNAL SEKOLAH), 2023)
Abstract: Development of Pop-Up Media Using Barcode Material on Ecosystems and Food Webs for Grade V Elementary School Students. The purpose of this study was to determine the validity, practicality and effectiveness of pop-up media in science learning material on the relationship between ecosystems and nets of class V SDN Sukorame 2 Kediri City. This study used the Research and Development (R&D) research method with the ADDIE model. The subjects of this study were teachers and fifth grade students at SDN Sukorame 2 Kediri City. There are two instruments used in this study, namely using a questionnaire and a test. The questionnaire is used to determine the validity of pop-up media using barcodes, material on pop-up media using barcodes, teacher and student responses. While the test is used to find out the effectiveness of pop-up media using barcodes. The results of research on the development of pop-up media using barcodes are as follows: (1) The results of the validity of pop-up media using barcodes get a percentage of 88.1%. very valid or can be used without revision. (2) The results of the post-test in a limited trial for pop-up media using barcodes obtained a classical completeness percentage of 80% and an extensive trial of 76.9% included in the very effective criteria. (3) The results of the teacher's response to pop-up media using a limited trial barcode obtained a percentage of 90.9% and a wide test of 92.7%. Student responses in the limited trial obtained a percentage of 96.8% and 95.6% in the wide trial. Declared very effective can be used without repair.Keywords: pop-up media, Research and Development (R&D), Material on Ecosystems and Food WebsAbstrak: Pengembangan Media Pop-Up Menggunakan Barcode Materi Ekosistem Dan Jaring-Jaring Makanan Untuk Siswa Kelas V Sekolah Dasar. “Tujuan penelitian ini untuk mengetahui kevalidan, kepraktisan dan keefektifan pada media popup pada pembelajaran IPA materi hubungan antara ekosistem dan jaring-jaring kelas V SDN Sukorame 2 Kota Kediri. Penelitian ini mengunakan metode penelitian Research and Developmen (R&D) dengan model ADDIE. Subjek penelitian ini adalah guru dan siswa kelas V SDN Sukorame 2 Kota Kediri. Instrument yang digunakan pada penelitian ini ada dua yaitu menggunakan angket dan tes. Angket digunakan untuk mengetahui kevalidan Media pop-up menggunakan barcode, materi pada media popup menggunakan barcode, respon guru dan siswa. Sedangkan tes digunakan untuk mengetahaui efektifitas media pop-up menggunakan barcode. Hasil dari penelitian pengembangan media pop-up menggunakan barcode adalah sebagai berikut: (1) Hasil validitas media pop-up menggunakan barcode di dapatkan presentase 88,1%. sangat valid atau dapat digunakan tanpa revisi. (2) Hasil post-test pada uji coba terbatas untuki media pop-up menggunakan barcode di dapatkan presentase ketuntasan klasikal sebesar 80% dan uji coba luas sebesar 76,9% masuk dalam kriteria sangat efektif. (3) Hasil respon guru pada media pop-up menggunakan barcode diuji coba terbatas didapatkan persentase sebesar 90,9% dan uji luas sebesar 92,7%. Respon siswa pada uji coba terbatas didapatkan persentase sebesar 96,8% dan uji coba luas sebesar 95,6%. Dinyatakan sangat efektif dapat digunakan tanpa perbaikan.”Kata Kunci: Media pop-up , Penelitian Penelitian dan Pengembangan, Materi Ekosistem Dan Jaring-Jaring Makanan